2018
DOI: 10.1038/s41598-018-22404-8
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department visits and unanticipated readmissions after liver transplantation: A retrospective observational study

Abstract: Improved survival after LT are likely to result in increased healthcare resource utilization. The pattern and risk factors of emergency department (ED) visits and unanticipated readmissions, associated cost, and predictors of healthcare resource utilization after liver transplantation (LT) patients who received LT between 2011 and 2014 were analyzed. A total of 430 LT recipients were enrolled and the 1 year all-cause mortality was 1.4%. ED visits occurred in 53% (229/430) and unanticipated readmissions occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
4
3
0
Order By: Relevance
“…The most common presenting complaints were GI symptoms (18%), infectious disease symptoms (9%), and respiratory symptoms (8%). These results were similar to those of the two studies done in South Korea and the US [ 13 , 17 ]. Contrary to our results, two other studies had different outcomes, with one study having infectious, gastrointestinal, and musculoskeletal symptoms as the most common presenting complaints [ 16 ], and the other study having electrolyte imbalance, gastrointestinal symptoms, and infectious symptoms as the most common presenting complaints [ 16 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The most common presenting complaints were GI symptoms (18%), infectious disease symptoms (9%), and respiratory symptoms (8%). These results were similar to those of the two studies done in South Korea and the US [ 13 , 17 ]. Contrary to our results, two other studies had different outcomes, with one study having infectious, gastrointestinal, and musculoskeletal symptoms as the most common presenting complaints [ 16 ], and the other study having electrolyte imbalance, gastrointestinal symptoms, and infectious symptoms as the most common presenting complaints [ 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…The study conducted in South Korea was more similar to this study’s methodology, with visits three years post-live transplant being assessed. Taking only the first three years into consideration, first-year ED presentations accounted for 59% of total visits in those years, which is comparable to the 64% in the Korean study [ 17 ]. Compared to previously mentioned studies, our study assessed the visits of patients after three years of discharge and found the visits to be as high as 26% of all visits assessed.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In order to assess the impact of readmission on long-term survival we looked at patient survival at 1 and 2 years after transplantation, and found that patients with at least one readmission had lower survival than those who were not readmitted. Similar results were found by several studies, showing that readmission is associated with lower long-term patient survival (2,3,6,8,(11)(12)(13). Emergency room visits may be an indicator of higher risk after liver transplantation.…”
Section: Discussionsupporting
confidence: 88%
“…In general, these patients are readmitted following presentation to either the ambulatory transplant clinic or ED. Although we do not have data on the number of patients that present to the ambulatory transplant clinic within 30 days post SOT, previous work has shown ED visits at 30 days to vary greatly between SOT groups (eg, as low as 17% for patients with kidney transplants, and as high as 44% for patients with liver transplants) [ 24 , 25 ]. Given this variability, we hypothesized a conservative estimate of 20% for our 30-day composite end point.…”
Section: Methodsmentioning
confidence: 99%